2013
DOI: 10.3389/fpsyt.2013.00102
|View full text |Cite
|
Sign up to set email alerts
|

Active Metabolites as Antidepressant Drugs: The Role of Norquetiapine in the Mechanism of Action of Quetiapine in the Treatment of Mood Disorders

Abstract: Active metabolites of some antipsychotic drugs exhibit pharmacodynamic and pharmacokinetic properties that may be similar to or differ from the original compound and that can be translated by a different profile of responses and interactions to clinical level. Some of these antipsychotics’ active metabolites might participate in mechanisms of antidepressant activity, as m-chlorophenylpiperazine (aripiprazole), 9-OH-risperidone and norquetiapine. Norquetiapine exhibits distinct pharmacological activity from que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…Noradrenaline and agonists of its receptors have also been shown to increase plasma concentration of anti-inflammatory cytokines, and decrease concentration of pro-inflammatory cytokines (Padro and Sanders, 2014). The action of norqetiapine to block noradrenaline uptake would lead to increased levels of noradrenaline in Pharmacology, Biochemistry and Behavior 135 (2015) 136-144 the brain (Lopez-Munoz and Alamo, 2013) and could in turn contribute to any anti-inflammatory effects of norquetiapine.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Noradrenaline and agonists of its receptors have also been shown to increase plasma concentration of anti-inflammatory cytokines, and decrease concentration of pro-inflammatory cytokines (Padro and Sanders, 2014). The action of norqetiapine to block noradrenaline uptake would lead to increased levels of noradrenaline in Pharmacology, Biochemistry and Behavior 135 (2015) 136-144 the brain (Lopez-Munoz and Alamo, 2013) and could in turn contribute to any anti-inflammatory effects of norquetiapine.…”
Section: Introductionmentioning
confidence: 97%
“…Both are antagonists at the dopamine D 1 and D 2 receptors, as well as the serotonin 5HT 2A receptor, which leads to a decrease in dopamine signalling. They are also both partial agonists at the presynaptic 5HT 1A receptor, while norquetiapine is a potent noradrenaline uptake inhibitor and increases noradrenaline function further by blocking presynaptic α 2 receptors (Lopez-Munoz and Alamo, 2013). Research has shown a role for both neurotransmitters such as 5-HT and dopamine, as well as the immune system in depression (Muller, 2014a) and possibly schizophrenia (Muller, 2014b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Physicochemical Properties of QTP and NQTP NQTP is an active metabolite of QTP with better kinetic binding parameters on target receptors and transporters including D 2 , 5HT 2A , 5HT 1A , NET, and α1b receptors 19) ; as such, bypassing the metabolic activation process from QTP to NQTP may account for less pharmacokinetic variability with NQTP compared to QTP. In the present study, NQTP was investigated as a drug candidate with improved biopharmaceutical properties compared to QTP.…”
Section: Resultsmentioning
confidence: 99%
“…Quetiapine is a CYP3A4 substrate, 9 and acts in part as a prodrug converting dopamine affinity quetiapine to more 5-hydroxytriptophan affinity norquetiapine. 10 Since the inducing effects of topiramate were recently reduced (less doses given per day), but the quetiapine dose was not changed, the quetiapine was now likely being converted from the dopamine blocking compound more slowly, producing more dopamine inhibiting effects. [9][10] Quetiapine, an atypical antipsychotic, does have reports of causing DIP, although much less commonly than other agents.…”
Section: Innovations In Pharmacymentioning
confidence: 99%